IMF Survey, Volume 36 Issue 09. (IMF Survey; IMF Survey ;, 2007)
IEO on IMF exchange rate advice; GFSR: financial system risks and issues for regulators; good times in Belgium; Africa's oil exporters; outlook for Middle East and Central Asia; Caucasus and Central Asia:capital flows; lessons from a decade of crises.